(untitled) (The Pretoria Student Law Review, 2025)
This note comments on the decision of the England and Wales Court of Appeal in R (on the application of McConnell) v Registrar General for England and Wales [2020] EWCA Civ 559. Freddy McConnell was registered as female at birth but transitioned at age 22 to live as a male. Mr McConnell was issued a certificate on 11 April 2017, confirming his gender as male. On 21 April 2017, Mr McConnell commenced fertility treatment. Upon giving birth to a son, Mr McConnell sought to register the birth of his son with the Registry Office. In a decision in January 2019, he was informed that he would have to be registered as the child’s ‘mother’. In this judgement, the Court of Appeal rejected McConnell’s contention that he should be registered as either the ‘father’ or ‘gestational parent’ as a matter of domestic law. Secondarily, it also held that this interpretation was not incompatible with articles 8 and 14 of the European Convention on Human Rights.